2019
DOI: 10.2147/cmar.s198886
|View full text |Cite
|
Sign up to set email alerts
|

<p>Exosomal miRNA-107 induces myeloid-derived suppressor cell expansion in gastric cancer</p>

Abstract: Background: Myeloid-derived suppressor cells (MDSCs) promote immunosuppression in the tumor microenvironment, support tumor growth and survival, and may contribute to immunotherapy resistance. Recent studies showed that tumor-derived exosomes (TDEs) can induce MDSCs accumulation and expansion, the mechanisms of which are largely unknown. Methods: The morphologies and sizes of the exosomes was observed by using a JEM-1400 transmission electron microscope. MicroRNA(miR)-107 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 52 publications
0
56
0
Order By: Relevance
“…Besides, JHD could affect the apoptosis, differentiation and immunosuppressive ability of MDSCs, possibly through multiple molecule signaling pathways, e.g. NF-kB (Flores et al, 2017), STAT-3 (Guha et al, 2019), HMGB1, AMPK (Salminen et al, 2019), microRNAs (Ren et al, 2019). However, we suspected that JHD plays multiple roles by regulating STAT-3, which was involved in processes such as cell transformation, expansion and activation of MDSCs (Panni et al, 2014;Pan et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Besides, JHD could affect the apoptosis, differentiation and immunosuppressive ability of MDSCs, possibly through multiple molecule signaling pathways, e.g. NF-kB (Flores et al, 2017), STAT-3 (Guha et al, 2019), HMGB1, AMPK (Salminen et al, 2019), microRNAs (Ren et al, 2019). However, we suspected that JHD plays multiple roles by regulating STAT-3, which was involved in processes such as cell transformation, expansion and activation of MDSCs (Panni et al, 2014;Pan et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Immunosuppressive [125] miR-24-3p NPC Immunosuppressive [126] miR-891a NPC Immunosuppressive [126] miR-106a-5p NPC Immunosuppressive [126] miR-20a-5p NPC Immunosuppressive [126] miR-1908 NPC Immunosuppressive [126] TAMs miR-222-3p EOC Immunosuppressive [127] miR-940 EOC Immunosuppressive [128] miR-21-3p EOC Immunosuppressive [129] miR-125b-5p EOC Immunosuppressive [129] miR-181d-5p EOC Immunosuppressive [129] miR-21 Head and neck cancer Immunosuppressive [130] miR-1246 Colon cancer Immunosuppressive [131] miR-16 Breast cancer Immunostimulatory [132] MDSCs miR-107 Gastric cancer Immunosuppressive [133] miR-21 OSCC Immunosuppressive [134] miR-21 Glioma Immunosuppressive [135] miR-10a Glioma Immunosuppressive [135] miR-29a Glioma Immunosuppressive [136] miR-92a Glioma Immunosuppressive [136] miR-155 CLL Immunosuppressive [137] CAFs miR-27a Gastric cancer Immunosuppressive [138] miR-1247-3p HCC Immunosuppressive [139] miR-21 HCC Immunosuppressive [140] NPC nasopharyngeal carcinoma, TAM tumor-associated macrophage, EOC epithelial ovarian cancer, MDSC myeloid-derived suppressor cell, OSCC oral squamous cell carcinoma, CLL chronic lymphocytic leukemia, CAF cancer-associated fibroblast, HCC hepatocellular carcinoma M2-like phenotype and suppressing the expression of M1 phenotype-associated markers [130]. Similarly, Cooks et al observed that cancer cells harboring TP53 mutation could reprogram neighboring TAMs into pro-tumor state via secreting miR-1246-enriched exosomes [131].…”
Section: Effector T Cells Mir-690 Melanomamentioning
confidence: 99%
“…Accumulating evidence has indicated that cancerderived exosomal miRNAs are capable of regulating the abundance and function of MDSCs [144]. Ren et al reported that gastric cancer cells enhanced the expansion and activity of MDSCs by delivering miRNA-107enriched exosomes [133]. Similarly, in the condition of hypoxia, glioma secreted exosomal miR-29a and miR-92a which enhanced the proliferation and function of MDSCs via targeting Hbp1 as well as Prkar1a [136].…”
Section: Cancer-derived Exosomal Mirnas and Mdscsmentioning
confidence: 99%
“…More recently, the microRNA cargo of TEVs was deeply investigated and associated with the TEV-mediated MDSC expansion. Gastric cancer EVs delivered miR-107 to MDSCs, targeting DICER1 and PTEN, thus contributing to cell expansion and activation [28]. Further, the in vivo injection of miR-107 to mice promoted the accumulation of MDSC in the peripheral blood [28].…”
Section: Tevs and Myeloid-derived Suppressor Cellsmentioning
confidence: 99%
“…Gastric cancer EVs delivered miR-107 to MDSCs, targeting DICER1 and PTEN, thus contributing to cell expansion and activation [28]. Further, the in vivo injection of miR-107 to mice promoted the accumulation of MDSC in the peripheral blood [28]. The MDSC-mediated immunosuppressive environment was largely described also in glioma [29]; recently, glioma-EVs were described as responsible for this event [30,31].…”
Section: Tevs and Myeloid-derived Suppressor Cellsmentioning
confidence: 99%